Development of Health-Promoting Measures for Working Conditions in Modern Horticulture and Viticulture Farms (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In recent years, horticulture and viticulture sectors have been expanding in Uzbekistan within the framework of agricultural modernization and cluster system development. However, working conditions in many farming enterprises still face a number of challenges. These include high temperature exposure, heavy physical workload, the impact of chemical agents (pesticides, carbon monoxide, nitrogen oxide, formaldehyde), and inadequate compliance with sanitary-hygienic standards. This paper analyzes these occupational risks and proposes practical and effective measures to improve the health and safety of workers. The suggested solutions aim to protect worker health, increase labor productivity, and ensure environmental safety.